INTERLANGUAGE OF LEARNER OF ENGLISH AS A FOREIGN LANGUAGE - Mrs FATIMAH, M.Appl.Ling. (Jurnal Humanitas)
In Indonesia, English is taught formally from the elementary school level until university. However, Indonesian learners of English face difficulties in producing certain grammatical features accurately, including the simple past tense. This study attempts to describe the common errors made by Indonesian learner of English in their spoken utterances. The data are obtained through interviews of four Indonesian postgraduate students. The data are analysed based on processes in error analysis. The study reveals that Indonesian postgraduate students still face problems in producing accurate grammatical features mainly on utterances containing simple past tense, plural form, and article ‘the’ and ‘a’. The production of past regular verbs is likely to be less accurate than that of past irregular verbs. The study also reveals that the source of learner’s errors might be due to the interference of L1, intralingual factors such as overgeneralization, incomplete application of rule in target language, and failure in comprehending the whole rule. There are also some possibilities that the errors made are evidence of transfer of training, strategies of L2 learning which enable the learner to communicate effectively during the conversation, and also the learner’s communication strategies.